Light-induced protein proximity by activation of gibberellic acid derivatives in living cells - Ziegler, Michael J.; Wombacher, Richard (Chemical tools for imaging, manipulating, and tracking biological systems, 2020)
Light controlled tools are highly attractive for the modulation and manipulation of biological processes. As an external trigger light can be applied with high temporal and special control to various samples. In the recent years a number of optochemical and -genetic tools have been developed to translate the input of light into molecular changes that result in specific biological responses. Here we present a highly efficient system for light-induced protein dimerization in live cells using photocaged derivatives of the plant hormone gibberellic acid (GA3). We provide a precise protocol for a simple one-step synthesis of the photocaged CIP and its application for protein translocation in living cells.